Pengaruh Short Message Service Reminder dan Diabetes Self Management Education berbasis Health Promotion Model terhadapkepatuhan pasien Diabetes Melitustipe 2 - Talango, Farid; Cahyaningtyas, Anindhita Yudha (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2024)
Compliance is the main key so that disease control can be controlled optimally, especially in patients with type 2 diabetes mellitus. Poor compliance behavior increases the risk of serious complications, reduced quality of life, morbidity and mortality, and costs for treatment. The aim of this research is to determine the effect of Short Message Service Reminder and Diabetes Self Management Education (DSME) based on the Health Promotion Model (HPM) on patient compliance with Type 2 Diabetes Mellitus. The design of this research is Quasi-experimental one group pretest-posttest. The sampling technique in this research was purposive sampling. The number of samples was 56 respondents. Wilcoxon test The instrument in this research is a questionnaire created by researchers which is used to determine compliance with type 2 diabetes mellitus treatment, which consists of 14 statement items. The results of the study showed that the level of compliance of respondents before the intervention was carried out mostly had a moderate level of compliance, namely 48 respondents (88%) and the level of compliance of respondents after the intervention was carried out mostly had a high level of compliance, namely 52 respondents (96%). The results of the Wilcoxon test analysis in the intervention group obtained a p value = 0.000. This shows that there is a significant difference in compliance between the pretest and posttest. Based on the results of this analysis test, it also shows that